Multiple intelligences and student achievement - Campbell, Linda
Finally, a book about multiple intelligences (MI) theory that answers the questions that all educational innovations must ultimately address: "What are the results on student achievement?" "How were those results achieved?" This book describes six schools that have used MI theory for five or more years. Through case studies of two elementary, two middle-level, and two high schools, Linda and Bruce Campbell illustrate why markedly different schools large and small, rich and poor, inner-city and suburban looked to MI when they wanted to boost student learning